Clinician-led evidence-based activism: a critical analysis. Issue 2 (15th March 2021) - Pushkar, Piyush; Tomkow, Louise
ABSTRACT: We introduce and critique a previously unexamined form of evidence-based activism (EBA): clinician-led evidence-based activism (CLEBA). In recent years funding of, and access to, the UK's National Health Service (NHS) have been depleted through cuts, privatisation, and the reduction of universal healthcare. In these austere and hostile times, the legitimacy of those drawing attention to resultant health inequalities is eroded. One tactic that doctors have adopted while advocating for the delegitimized has been CLEBA: strategic use of clinical authority in the production and mobilization of knowledge for the governance of health issues. To illustrate the concept, we analyse two cases of CLEBA in the NHS in which we have participated. The first resisting cuts and privatisation of the NHS, the second resisting the charging of forced migrants for healthcare. By analysing CLEBA as a tactic, we show how doctors work to effect progressive goals by lending legitimacy to their allies, who are delegitimised by opponents as 'loony-left', 'shroud-waving' 'health tourists'. This approach to the problem of legitimacy separates CLEBA from EBA. Whereas EBA seeks to rebalance unequal social relations within a doctor-patient collective, CLEBA capitalizes on the symbolic power of doctors to contest unequal social relations out with the collective. By lending clinical authority to activist discourses, CLEBA consolidates forms of collective agency in which certain actors remain illegitimate. In contrast with EBA, where the rebalancing of legitimacy itself is prioritized, CLEBA reinforces a hierarchy of legitimacy that places clinicians on top.